Analysis of Fraudulent Financial Statements Using the Perspective of Fraud Hexagon Theory - Meldica Widya Ningrum; Nanik Sri Utaminingsih (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This study aims to analyse the effect of the fraud hexagon theory, which includes financial stability, change in director, nature of industry, auditor changes, frequency of CEO pictures, and related party transactions on fraudulent financial statements. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The sampling technique used was purposive, yielding a total of 154 units of analysis. This study uses secondary data with documentation techniques. The data were analysed using panel data regression in EViews 13. The results of this study indicate that the nature of the industry, the frequency of CEO photographs, and related-party transactions have a significant positive effect on fraudulent financial statements. Auditor changes have a significant negative effect on fraudulent financial statements. Neither financial stability nor a change in directors affects the issuance of fraudulent financial statements. This study uses the perspective of hexagon theory, with related party transactions and asset composition as proxies, both of which are still rarely researched. A sample of companies in the mining sector was selected because, according to ACFE 2024, the sector has experienced the largest fraud losses worldwide.